Lifestyle intervention for the management of chronic noncommunicable diseases: hypertension, dyslipidemia, insulin resistance and overweight in a male patient. Case Report: Intervención en estilos de vida para manejo de enfermedades crónicas no transmisibles: hipertensión arterial, dislipidemia, resistencia a la insulina y sobrepeso en paciente masculino. Reporte de Caso - Delorenzo Ch, Natalia (2021)
Chronic noncommunicable diseases (NCDs) are defined as diseases of long duration, slow progression, that do not resolve spontaneously and that rarely achieve complete cure (1). Cardiovascular diseases (CVD), cancer, chronic respiratory diseases and diabetes stand out. NCDs cause 41 million deaths each year (71% of the world total). Cardiovascular disease accounts for the majority of these deaths (17.9 million per year) (2). In addition to causing premature deaths, these diseases lead to complications and disabilities, limit productivity, and drug treatments are expensive, so early detection and timely treatment should be a priority (2). Lifestyle medicine (MEV) has gained relevance in the prevention, treatment and reversal of most NCDs, directly addressing their causes (3). We will present the case of a young man with multiple risk factors and a diagnosis of arterial hypertension, dyslipidemia and insulin resistance. We carry out an intervention through the MEV to improve the patient's condition and health. At the 6-month follow-up, significant changes in habits and laboratory parameters were achieved.